GEOCHEMICAL AND MINERALOGICAL CHARACTERIZATION OF DETRITAL SEDIMENT AND LATERIZED BRECCIA DEPOSIT, ROUTA DISTRICT, KONAWE REGENCY - Noor Setiadi, Imam
Nickel laterite deposits associated with the weathering of ultramafic rocks are the current target for nickel production, but there are conditions that cause laterite deposits to be displaced and redeposited in lower land as detrital sediment deposits. Due to environmental changes and the contribution of other materials during the processes of transport and redeposition, detrital sediment deposits exhibit characteristics that differ from their original source material. A comprehensive understanding of the geochemical and mineralogical characteristics is essential to unravel the formation process of detrital sediment deposits, which encompass the displaced limonite, brown sediment, black sediment, gray sediment, as well as the peridotite breccia unit and its weathering product, laterized breccia. Several methods were carried out including petrographic analysis of core samples of sandstone and outcrop samples of peridotite breccia, stereographic and kinematic projections of structural data accompanied by LiDAR to support lineament identification. In addition, statistical analysis was performed on geochemical data obtained from X-ray fluorescence (XRF) testing using univariate and multivariate approaches, including principal component analysis (PCA) and correlation matrix. Mineralogical characterization through X-ray powder diffraction (XRPD) analysis was also conducted to determine the mineralogical properties of each layer and provide insights into the geological conditions of the study area. Petrographic analysis results reveal that the sandstones, ranging from medium to very fine-grained, deposited in the study area are classified as feldspathic wacke and lithic wacke. In contrast, breccia samples exhibit a monomictic texture dominated by peridotite clasts. Stereographic projections and kinematic analyses indicate that the study area was shaped by persistent and intense structural processes trending predominantly south-southeast and west-southwest, resulting in surface uplift and subsidence that formed basins during the Miocene. These features were subsequently intersected by sinistral strike-slip faults. Geochemical analysis reveals an increase in sulphur content within the brown sediment and black sediment units. This indicates the influence of organic material decomposition, supported by significant carbon content. Changes in the composition of iron oxide minerals, such as the transformation of goethite into iron carbonate minerals like siderite, serve as indicators of an environmental shift from oxidative to reductive conditions. Oxidative environments are characterized by the displaced limonite unit, which exhibits geochemical features of MgO <3.5 wt% and is predominantly composed of goethite and kaolinite. This layer is interpreted as the product of weathering of ultramafic rocks, followed by erosion and transport to lower areas. The presence of potassium-rich clay minerals in laterite deposits is considered unusual; however, this can be explained by the dissolution of potassium during the transport and deposition processes from minerals such as K-feldspar, biotite, or chlorite. In the gray sediment unit, potassium subsequently associates with aluminosilicate compounds to form illite minerals. The geochemical characteristics of this layer with K?O content ?0.15 wt%. The laterized breccia unit exhibits a moderate degree of weathering, dominated by iron oxide minerals such as goethite, alteration minerals like lizardite, and silica precipitation. Furthermore, a sulphur content of <0.015 wt% indicates that its formation was neither influenced by organic material nor associated with anaerobic environmental conditions. This evidence confirms that this layer is a product of weathering of peridotite breccia, commonly found alongside it within the laterite deposit profiles of the study area.